Agricultural and Food Waste Analysis, Characterization, and Extraction of Bioactive Compounds and Their Possible Utilization - Dueñas Paton, Montserrat; García-Estévez, Ignacio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The food processing industries produce millions of tons of losses and waste during processing, which are becoming a grave economic, environmental, and nutritional problem. Fruit, vegetable, and food industrial solid waste include leaves, peels, pomace, skins, rinds pulp, stems, seeds, twigs, and spoiled fruits and vegetables, among other waste released in food production, which can be formed during cleaning, processing, cooking, and/or packaging. These wastes are characterized by being an important source of bioactive compounds, such as phenolic compounds, dietary fibers, polysaccharides, vitamins, carotenoids, pigments, and oils, among others. These bioactive compounds are closely associated with beneficial effects on human health. These by-products can be exploited in different industries: in food industries for the development of functional ingredients and/or new foods or natural additives; in pharmaceutical industries for medicinal, healthcare, or cosmetic products; in agricultural industries as fertilizers or animal feed; and in chemical industries, among others. The reutilization of these by-products will ensure the sustainable development of food industries and reduce their environmental impact, which will contribute to the fight against environmental problems, leading to potential mitigation of climatic change. Therefore, the determination of bioactive compound composition in agricultural and food waste and the production of extracts containing these compounds is the first step towards its reutilization.